Open-Circuit Voltage Decay Simulations on Silicon and Gallium Arsenide p-n Homojunctions: Design Influences on Bulk Lifetime Extraction. (July 2020) - Lemaire, A.; Perona, A.; Caussanel, M.; Dollet, A.
Abstract: Open-Circuit Voltage Decay (OCVD) method was investigated for few decades as a simple and convenient method to characterize effective lifetime into Ge and Si p-n homojunctions. Minority carrier lifetime (MCL) is an important parameter to optimize device design where being able to investigate one type of carriers is an important goal. The p-n homojunction design is of major importance to reach that purpose by OCVD. We carried out Technology Computer Aided-Design simulations of the OCVD signal. The study focused on Si and GaAs p-n homojunctions. We looked into bulk thickness and doping level influences on bulk lifetime extraction. Previously, those influences have not been quantified for Si and never investigated for GaAs. MCL accurate extraction from bulk required a bulk thickness at least 4 times higher than diffusion length and emitter doping levels at least 2 orders of magnitude higher than bulk. Likewise, the paper shows different accuracy of extraction between GaAs/Si and p-type/n-type bulk in p-n homojunction.